FAKTOR-FAKTOR PENOLAKAN MEREK COKLAT CHACHA OLEH KEMENKUMHAM BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 - Arif Rahman; Syuryani Syuryani; Jasman Nazar (Ensiklopedia of Journal, 2023)
The author conducted this research motivated by the author's curiosity about the factors of rejection of the chacha chocolate brand by the Ministry of Law and Human Rights based on law number 20 of 2016. This research is a type of normative juridical legal research that is descriptive in nature. The types of data used are primary data and secondary data. The data sources used are primary data sources and secondary data sources. The data collection technique used was literature study, in which case the library materials used were books, laws and regulations and law magazines. Based on the results of the research and analysis obtained, it can be concluded that the settlement of the case against the rejection of the chacha brand by the Ministry of Law and Human Rights is to reject the Delfi chacha brand because it has similarities in principle to the chacha brand that was circulating in 2012. It was also stated that Delfi chacha could not prove the argument for the lawsuit if the brand was a common word both from witnesses and experts. And this is the reason why Delfi Chacha does not get legal protection because his brand has similarities in principle to other parties' brands and there is no element of difference.